Corporate Social Responsibility in the Context of Financial Crisis: A Comparison between Romania and Lithuania - Rodica Milena Zaharia; Dainora Grundey (Amfiteatru Economic Journal, 2011)
The paper aims to identify the link between the corporate social responsibility (CSR) and the recent financial crisis, and to determine the main features of the companies' responsible behavior during this period. This inquiry follows the pattern of a descriptive study and will concentrate on the search of the literature, in order to identify the relationship between the present financial crisis and CSR, and the corporate behavior in this period. Companies' reports, and discourses on CSR will be considered to characterize firms' behavior. Examples of CSR from Romania and Lithuania are offered in order to illustrate the conclusions of the paper. The investigation of the literature leads to two major conclusions. One conclusion of the paper is that CSR is on a turning point and it is expected that a new orientation toward theoretical and practical approaches regarding the concept will be developed after this crisis. The other outcome reveals the contradiction between discourse and action: companies' priorities in crisis time are more concentrated on financial aspects; even if at the discourse level all companies declare their commitment to responsible actions.
Keywords: M14; M31; D03; N14; 330; corporate social responsibility; financial crisis; business; Romania; Lithuania